2017
DOI: 10.1097/yic.0000000000000155
|View full text |Cite
|
Sign up to set email alerts
|

The impact of paliperidone palmitate long-acting injection on hospital admissions in a mental health setting

Abstract: We screened 216 patients in a retrospective observational investigator-initiated study, of whom 45.37% patients (n=98) were retained after the inclusion criteria were applied. These patients had been prescribed paliperidone palmitate long-acting injection (PPLAI) with diagnoses of schizophrenia, schizoaffective disorder and bipolar affective disorder. We investigated whether PPLAI has an effect on the frequency and length of admissions to mental health inpatient units, the number of contacts with Crisis Resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 10 publications
0
13
2
Order By: Relevance
“…Interestingly, lower rates of discontinuation have been reported with paliperidone palmitate at 1 year in a similar population to those in our study. 15 , 16 However, both these studies included patients who were outpatients stabilized on medication, as well as inpatients. A higher discontinuation rate may have been expected in our study, which included only patients admitted to an inpatient unit following a relapse in their mental state.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lower rates of discontinuation have been reported with paliperidone palmitate at 1 year in a similar population to those in our study. 15 , 16 However, both these studies included patients who were outpatients stabilized on medication, as well as inpatients. A higher discontinuation rate may have been expected in our study, which included only patients admitted to an inpatient unit following a relapse in their mental state.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study the rate of dropouts increased dramatically during the 3‐year follow‐up period. The main reasons for discontinuation were the onset of adverse effects and patient perceived ineffectiveness.…”
Section: Resultsmentioning
confidence: 97%
“…47,[49][50][51]53,55 The only study reporting the advantage of PP1M on oral antipsychotics showed several limitations, the main being a suboptimal statistical power due to the small sample size and the inclusion in the study cohort of both new and old PP1M users. 54 The main causes of drug discontinuation before the planned study end were adverse events 45,46,61,62,65 and ineffectiveness. 47,51,59,62,65,66 The two available long-term studies on PPM3 showed a rate of premature discontinuation similar to that shown by the active comparator (PP1M).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, LAI products show a higher cost/effectiveness compared to oral antipsychotic treatment (Yang et al 2009) with reduced hospital admissions, relapse rates and length of inpatient stay, especially for patients who may be at risk of non-adherence with oral antipsychotics (Peng et al 2011;Nikolić et al 2017).…”
Section: Technological and Regulatory Barriersmentioning
confidence: 99%